REFERENCES OF THE RURAL AND URBAN POPULATION ON HYPERTENSIVE DISEASE IN HYPERTENSIVE PATIENTS - Bazirgon Shokirovich Ruzmetov; Nazira Azizovna Narmukhamedova (Scholar Express Journals, 2021)
In the following years it is known from a large amount of literature and statistics that not only in our country but also in many countries of the world the growth and rejuvenation of flatulence is observed. In the Russian Federation at present 30-49 % of adult population have blood pressure higher than 140/90 mm Hg and its survival is observed. In developed countries, 5- 15%, in Russia 20.2% of pregnant women have high blood pressure.
Keywords: Hypertension; Khorezm Region; Rural And Urban Population